The effects of the financial markets on the real economy: a look at developing markets - Matos, João Filipe da Silva (2019)
The importance of understanding the role of the financial system in today’s economy is clearer than ever. As such this study was conducted to assess the links between financial development and the real economy and whether the financial system is fulfilling its role in supporting investment and growth. The study used a Correlations analysis together with a Granger Causality analysis and a VEC Model to obtain its results. They indicate there is indeed a relationship between financial development and investment as well as economic growth. Specifically both the development of public financial markets and private institutional markets contribute towards more investment. However, while public financial markets seem to have a positive relationship with economic growth, results point to private institutional markets having a negative relationship.